Basic determinants оf audit sampling with overview on practice in republic of Srpska - Дарко Томаш, M.Sc. (Acta Economica, 2008)
In frst stages of development of the auditing profession it was not unusual for the auditor to review nearly entire accounting records of the audited company. However, with companies’ growth, both in size and in complexity, it became cost-ineffcient to assess the complete documentation. Audit of fnancial reports in large companies, with huge number of transactions, would not be possible if auditors attempted to check each and every transaction, amount and balance. Even in case that such attempt was possible, described audit approach would certainly initiate the question regarding appropriateness of the audit, considering the fact that demanded information would not be available at desired time. Conversely, audit costs would be enormously increased, which would additionally intensify this issue. In these cases, auditor may select one sample of items or transactions that will be subject to auditing procedures, in which manner he/she can attain reasonable assurance on audited fnancial reports.